Protocol for the effect evaluation of independent medical evaluation after six months sick leave: a randomized controlled trial of independent medical evaluation versus treatment as usual in Norway - Elisabeth Husabo; Karin Monstad; Tor Helge Holmås; Irene Oyeflaten; Erik L. Werner; Silje Maeland (BMC, 2017)
Abstract Background It has been discussed whether the relationship between a patient on sick leave and his/her general practitioner (GP) is too close, as this may hinder the GP's objective evaluation of need for sick leave. Independent medical evaluation involves an independent physician consulting the patient. This could lead to new perspectives on sick leave and how to follow-up the patient. Methods/design The current study is a randomized controlled trial in a Norwegian primary care context, involving an effect evaluation, a cost/benefit analysis, and a qualitative evaluation. Independent medical evaluation will be compared to treatment as usual, i.e., the physicians' and social insurance agencies' current management of long-term sick-listed patients. Individuals aged 18-65 years, sick listed by their GP and on full or partial sick leave for the past 6 months in Hordaland county will be included. Exclusion criteria are pregnancy, cancer, dementia or an ICD-10 diagnosis. A total sample of 3800 will be randomly assigned to either independent medical evaluation or treatment as usual. Official register data will be used to measure the primary outcome; change in sickness benefits at 7, 9 and 12 months. Sick listed in other counties will serve as a second control group, if appropriate under the "common trend" assumption. Discussion The Norwegian effect evaluation of independent medical evaluation after 6 months sick leave is a large randomized controlled trial, and the first of its kind, to evaluate this type of intervention as a means of getting people back to work after long-term sickness absence. Trial registration ClinicalTrials.gov NCT02524392 . Registered June 23, 2015.